PERAN ORANG TUA DALAM MEMBENTUK KARAKTER SISWA BUDDHIS DI SD NEGERI MOJOREJO 01 KOTA BATU - I Putu Widiana I Putu Widiana (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2021)
This research examines the role of parents in shaping character of Buddhist students. The background of this research is there are students who are shy, difficult to hang out, problems in their education and there are children with special needs. Therefore, this study aims to determine the character of students and to know the role of parents in shaping character. The research method used descriptive qualitative. The informants in this study were five parents, five students and one teacher. The research was conducted at SD Negeri Mojorejo 01, Batu City. Data collection techniques were obtained from observations, interviews and documentation. The results showed that students of SD Negeri Mojorejo 01, had quite good characters, this was obtained based on data obtained through interviews. To find out character of students, it is necessary to observe at school and home. Realizing student character can be done through habituation by applying Buddhist values.